Identifikasi Air Tanah Di Daerah Sekitar Jalan Tunas Harapan Desa Pal IX Menggunakan Metode Vertical Electrical Sounding (VES) - Danti, Namira; Zulfian, Zulfian; Perdhana, Radhitya (JFT : Jurnal Fisika dan Terapannya, 2025)
A hydrogeological investigation using the Vertical Electrical Sounding (VES) method was conducted in the vicinity of Jalan Tunas Harapan, Pal IX Village, to determine groundwater potential. The data acquisition involved four VES points with an inter-point spacing of 60 m-80 m. Inversion results yielded resistivity values ranging from 2.11 Ωm-203 Ωm, revealing subsurface lithology composed of clay, wet clay, sandy silt, and clayey sand layers. Groundwater potential was identified within the clayey sand layer (191 Ωm-203 Ωm), which is distributed across all four VES points. This layer is found at depths of 35.2 m-71.3 m in VES 01, 35.4 m-69.1 m in VES 02, 34.7 m-64.7 m in VES 03, and 33.3 m-67.1 m in VES 04.  These findings imply that the clayey sand layer functions as a viable aquifer zone capable of supporting groundwater availability. Based on the interpretation, groundwater drilling in the study area is recommended within the depth interval of 33.3 m-71.3 m.